Analisis Kesalahan Matematis Mahasiswa Teknik Sipil pada Mata Kuliah Kalkulus II - Zukhrufurrohmah Zukhrufurrohmah; Adi Slamet Kusumawardana (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
This research’s purpose is to describe the mathematical errors of civil engineer college students in subject Calculus II. The research’s method uses a qualitative approach that are reducing data, serving data, and conclude. Based on the research, it found that the major error to solve the problems of Calculus II is manipulating algebra form. The error of calculating is the second one after the error of manipulating algebra form. The researcher also finds that even the college students choose the right formula to solve the problems, they make an error in implementing the formula that they were chosen.